2010
DOI: 10.1001/archsurg.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Most Severely Injured Spleen

Abstract: Nearly two-thirds of patients with grade IV or V BSI require surgery. A grade V BSI and brain injury predict failure of NOM. This data must be taken into account when generalizations are made about the overall high success rates of NOM, which do not represent severe BSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 21 publications
1
34
2
Order By: Relevance
“…Consequently, most patients will respond to non-operative treatment. Our personal results support the principle of conservative treatment in all haemodynamically stable patients, with overall efficacy rate more than 91%, as was reported in modern literature (7,8).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, most patients will respond to non-operative treatment. Our personal results support the principle of conservative treatment in all haemodynamically stable patients, with overall efficacy rate more than 91%, as was reported in modern literature (7,8).…”
Section: Discussionsupporting
confidence: 90%
“…and Wahl et al [10,21] treated HDS patients with NOM and hemodynamically unstable patients with OM. Blood pressure values were reported only in 10 studies [9-11,13,17,18,20-22,24], seven studies [9,10,16,18,20,22,24] reported the median systolic blood pressure, two studies [11,13] reported the number of patients with blood pressure above or below 90 mmHg and one study [21] reported the mean systolic/diastolic blood pressure. One study did not specify blood pressure criteria for NOM or OM [9].…”
Section: Methodsmentioning
confidence: 99%
“…ISS was reported in 19 studies: mean value was reported in 3 studies [8,12,19], median value ± SD in 14 studies [1,6,7,9,10,14,16-18,20,22-25], the range of ISS was reported in 1 study [11], while in another study [13] ISS was defined with values above or below a cut-off of 25. It was possible to extrapolate the ISS value for the patients in the two compared groups (NOM vs .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations